Culture media for food microbiology (Elsevier, 1995)
This publication deals in depth with a limited number of culture media used in Food Science laboratories. It is basically divided into two main sections: Data on the composition, preparation, mode of use and quality control of various culture media used for the detection of food borne microbes; Reviews of several of these media, considering their selectivity and productivity and comparative performance of alternative media. Microbiologists specializing in food and related areas will find this book particularly useful.